HABITUS PEMAIN GAME ONLINE DALAM KEKERASAN VERBAL DI WARUNG KOPI: - - Muhammad Afnizal; Harmona Daulay; T. Ilham Saladin; Hadriana Marhaeini Munthe; Linda Elida (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
All processes of social interaction in humans are important, including being useful as an effort to build relationships between them. One form of social interaction that occurs in humans is playing. The sophistication of adult technology now presents various developments in playing such as online games. The process of playing online games is proven to leave various kinds of social problems, including verbal violence. This research is a case study using a qualitative method that aims to look deeper into the phenomenon of verbal violence that occurs among online game players in coffee shops which are a forum for social interaction for the surrounding community, located in Lhokseumawe City, in Aceh's construction as Veranda of Mecca. The research subjects were verbal violence in online games, and the objects of this research were academics, community leaders, and online game players. Data collection techniques through observation, documentation, and in-depth interviews using the habitus theory approach. The results of the study show that the neglect of cultural values and the Islamic Shari'a system by online game players triggers verbal violence behavior. In line with these conditions, other variables that become triggers are self-principles, stress, opponents at play, imitating behavior and weak supervision and application of rules.